ЕБС-ийн англи хэлний сургалтын амжилт, түүнд нөлөөлж буй хүчин зүйлсийг харьцуулан судлах нь: Comparative Study on Success Factors of Quality English Education at Secondary Schools - E., Erdenetuya; A., Enkhtuya (Mongolian Journal of Foreign Languages and Cultures, 2023)
Students admitted to the National University of Mongolia following their completion of high education are required to study 6 credit hours of Academic English in intermediate and upper levels as part of the university foundation program to be able to eventually satisfy the university commencement requirement ruling upper-intermediate level English language proficiency by the time of graduation. Nevertheless, despite the seven years of continuous study of English language at previous levels of education (primary, secondary and high), the students often fall short of English language competence sufficient to take the course and continue their English language learning in intermediate level at the university. Consequently, the university encounters a need to lower the course content level, open beginner or lower-intermediate level classes for those students and repeat the same contents that had been already covered over the past 7-9 years at primary, secondary and high schools. Although such a solution may seem to temporarily answer the student need, in the long run, it will bring massive negative consequences to the university in relation to the implementation of their own program and achievement to their declared objective to prepare skilled workforce with excellent English language proficiency. With this situation and consequences in mind, we conducted this research to inspect if the English language programs implemented at primary, secondary, high schools are bringing the academic success expected/ruled by their core curriculum, and if the success differs between the state-owned and privately- owned schools (excluding the specialized English language schools), and in case of observation of any major difference in academic success between the state-owned and privately-owned schools, identify the factors that negatively or positively influence the success from which possible solutions for improvement can be derived.